2022
DOI: 10.3390/ijerph19020674
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Plants and Microorganisms Mediated Synthesis of Silver Nanoparticles, Role of Plants Metabolites and Applications

Abstract: Silver nanoparticles are one of the most extensively studied nanomaterials due to their high stability and low chemical reactivity in comparison to other metals. They are commonly synthesized using toxic chemical reducing agents which reduce metal ions into uncharged nanoparticles. However, in the last few decades, several efforts were made to develop green synthesis methods to avoid the use of hazardous materials. The natural biomolecules found in plants such as proteins/enzymes, amino acids, polysaccharides,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
87
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(90 citation statements)
references
References 123 publications
0
87
0
3
Order By: Relevance
“…The reducing potential of different classes of plant secondary metabolites to synthesize nanoparticles has been excellently reviewed [ 46 , 47 ]. Biomolecules with various structural classes, such as phenolics, flavonoids, terpenoids, saponins, alkaloids, etc., that are present in plant extracts may be involved as reducing and stabilizing agents in nanoparticles synthesis; however, complexity regarding the exact mechanism of synthesis exists [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reducing potential of different classes of plant secondary metabolites to synthesize nanoparticles has been excellently reviewed [ 46 , 47 ]. Biomolecules with various structural classes, such as phenolics, flavonoids, terpenoids, saponins, alkaloids, etc., that are present in plant extracts may be involved as reducing and stabilizing agents in nanoparticles synthesis; however, complexity regarding the exact mechanism of synthesis exists [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, as was already indicated in this work, the green synthesis of AgNPs using different plant extracts can be assessed as a replacement for the chemical and physical synthesis methods used at this time. Until now, many researchers interpreted and used various vegetal products, such as leaves, barks, fruits, roots and seeds, for the synthesis of NPs [ 114 , 115 ]. Given the fact that, green synthesis is environment friendly and having no toxicity effects, this approach opens a new era of safe nanotechnology [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the manufacturing of nanoparticles by biological methods has emerged as a new trend in the industry due to its nontoxicity, repeatability, ease of scaling up, and well-defined shape. Researchers have found that novel resources such as microbes and plants have the most potential for producing nanoparticles ( Shafey, 2020 ; Lahiri et al, 2021 ; Cuong et al, 2022 ; Devra, 2022 ; Ettadili et al, 2022 ; LomelĂ­-Rosales et al, 2022 ; Majeed et al, 2022 ; Mustapha et al, 2022 ; Najafi et al, 2022 ). Metal nanoparticles have been synthesized using a variety of microorganisms, including bacteria, fungus, and yeast, as well as plants.…”
Section: Introductionmentioning
confidence: 99%